The role of the religious scholars of Faqih Ali Dato’ Maharaja’s descent in upholding sharia implementation in Terengganu - Wan Ahmad Fauzi, Wan Husain; Wan Rohaida, Wan Husain; Hanif, Md Lateh (Universiti Sains Islam Malaysia, 2024)
Faqih Ali Dato’ Maharaja is a well-known figure among local historians, particularly among those who study prominent religious scholars in Southeast Asia. His descendants contributed significantly to promoting the sustainability of Islamic teaching in Terengganu. Islam was upheld as the principle of Terengganu's sovereignty, forming the basis of its constitutional system, thus legitimizing the position of Sharia as the law of the land. This was manifested on the Inscribed Stone dated 4 Rejab 702H. Nevertheless, the role of the descendants of Faqih Ali have not been a focal point in academic writing. The paucity of literature and elucidation within this domain serves as the basis for this study. This article aims to investigate the role of prominent religious scholars of Faqih Ali Dato’ Maharaja's descent in upholding the implementation of Sharia in the Terengganu Sultanate until the Independence Day of Tanah Melayu in 1957. This study is qualitative in nature and employs historical research methods. Data were obtained from archival documents, government publications, field research, and secondary sources. Findings show that the preservation of the Sharia legacy in Terengganu since the discovery of the Inscribed Stone was influenced significantly by the substantial contributions of religious scholars who were also the administrators of Faqih Ali Dato’ Maharaja’s descent, evidenced by the legislation of Itqanul Muluk bi Ta'dil al-Suluk in 1911 and its extension, the Terengganu State Constitution. Hence, the practice of Sharia before 1957, was not confined to personal affairs as understood by many; by virtue of the Federal Constitution, the public affairs of Sharia are now entrusted to public authorities at the federal level unless those matters are retained in the state administration.